The Influence of Education and Training (Diklat), Competency on Position Promotion and Employee Performance of Eco Beach Villa and Apartment Canggu - Wibisono, Gunawan; Nugraha, Surya (Akademi Komunitas MAPINDO, 2023)
This research aims to analyze the influence of education and training (Diklat), competency on position promotion and employee performance at Eco Beach Villa and Canggu Apartments in companies in the tourism industry sector in Badung district. In this study, the population studied was 216 permanent employees at Eco Beach Villa and Apartment Canggu. This research sample used the Solvin formula to obtain 68 people. The analysis technique used is